Six genetically linked mutations in the CD36 gene significantly delay the onset of Alzheimer's disease - Šerý, Omar; Zeman, Tomáš; Sheardová, Kateřina; Vyhnálek, Martin; Marková, Hana; Laczó, Jan; Lochman, Jan; Kralik, Petr; Vrzalová, Kamila; Dziedzinska, Radka; Balcar, Vladimir J; Hort, Jakub (Scientific reports, 2022)
The risk of Alzheimer's disease (AD) has a strong genetic component, also in the case of late-onset AD (LOAD). Attempts to sequence whole genome in large populations of subjects have identified only a few mutations common to most of the patients with AD. Targeting smaller well-characterized groups of subjects where specific genetic variations in selected genes could be related to precisely defined psychological traits typical of dementia is needed to better understand the heritability of AD. More than one thousand participants, categorized according to cognitive deficits, were assessed using 14 psychometric tests evaluating performance in five cognitive domains (attention/working memory, memory, language, executive functions, visuospatial functions). CD36 was selected as a gene previously shown to be implicated in the etiology of AD. A total of 174 polymorphisms were tested for associations with cognition-related traits and other AD-relevant data using the next generation sequencing. Several associations between single nucleotide polymorphisms (SNP's) and the cognitive deficits have been found (rs12667404 with language performance, rs3211827 and rs41272372 with executive functions, rs137984792 with visuospatial performance). The most prominent association was found between a group of genotypes in six genetically linked and the age at which the AD patients presented with, or developed, a full-blown dementia. The identified alleles appear to be associated with a delay in the onset of LOAD. In silico studies suggested that the SNP's alter the expression of CD36 thus potentially affecting CD36-related neuroinflammation and other molecular and cellular mechanisms known to be involved in the neuronal loss leading to AD. The main outcome of the study is an identification of a set of six new mutations apparently conferring a distinct protection against AD and delaying the onset by about 8 years. Additional mutations in CD36 associated with certain traits characteristic of the cognitive decline in AD have also been found.
Keywords: antigeny CD36; CD36 Antigens; Neuropsychological Tests; neuropsychologické testy; Executive Function; Alzheimerova nemoc; Alzheimer Disease; Mutation; mutace; Polymorphism, Single Nucleotide; lidé; exekutivní funkce; jednonukleotidový polymorfismus; Humans